Sistemas de consórcios de milho associado a doses de nitrogênio e seus reflexos no feijão coinoculado em sucessão - Chaves, Diego Rubião [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The diversification (intercropping and succession) of crops associated with the reduction of nitrogen fertilization are sustainable, innovative and low-cost agricultural practices and can increase grain productivity and the contribution of carbon and nitrogen in the soil-plant system. The objective of the project was to evaluate the effects of growing second-crop corn single and intercropped with cover crops associated with doses of nitrogen in top dressing, and its effects on the development and productivity of beans subjected to a reduction in the dose of nitrogen fertilizer in top dressing in succession. . The research project was developed in two stages during the autumn-winter in the municipality of Dracena, SP and an area irrigated by sprinkler. The first subproject was carried out in a randomized block experimental design in a 4x4 factorial scheme, consisting of single corn and intercropped with cover crops (Crotalaria spectabilis, Urochloa ruziziensis and C. spectabilis + U. ruziziensis) and four doses of nitrogen (zero, 40, 80 and 120 kg ha-1) using urea in coverage with half (50%) of the dose at stage V5 and half (50%) at stage V8, with four replications, the entire area received application of Azospirillum brasilense at stage V4. In the second subproject, the experimental design was in randomized blocks arranged in a 4x4x2 factorial scheme for beans, with four replications, coinoculated (Rhizobium tropici + Azospirillum brasilense) in succession, subjected to application of 50% and 100% of the recommended dose of nitrogen fertilizer in top dressing. Assessments carried out in corn cultivation: plant dry matter, photosynthetically active radiation, leaf nitrogen content, leaf chlorophyll index, final plant population, average plant height, ear insertion height, stem diameter, number of rows of grains per ear, number of grains per row, mass of one hundred grains and grain yield. The following were evaluated in the bean crop: plant population, plant dry matter, photosynthetically active radiation, leaf nitrogen content, leaf chlorophyll index, number of pods per plant, number of grains per plant, average number of grains per pod, mass of one hundred grains, grain productivity and crop cycle. The intercropping system between corn + Crotalaria spectabilis increases the concentration of foliar nitrogen in corn, however, similar to single corn cultivation. The consortia between corn + Urochloa ruziziensis associated with doses of zero and 40 kg ha-1 of N and between corn + C. spectabilis + U. ruziziensis associated with doses of 80 kg ha-1 of N in coverage provided the highest grain yields of corn. The dose of 40 kg ha-1 of N showed superior results in intercrops between corn + C. spectabilis and corn + U. ruziziensis for dry mass of corn plants as well as single corn. In the consortium between corn + C. spectabilis associated with zero nitrogen dose, a greater accumulation of dry matter was observed in the bean plant due to the residual effect. In intercropping systems between corn + C. spectabilis (2,753 kg ha-1) and between corn + U. ruziziensis (2,717 kg ha-1) alone, it results in 10% increases in bean grain productivity when compared to single corn ( 2,488 kg ha-1). The consortium between corn + C. spectabilis associated with doses of 0 kg ha-1 N provided the highest bean productivity (3,168 kg ha-1).
Consortium of corn with ground cover crops associated 2 with nitrogen supply
Keywords: Zea mays L.; Crotalaria spectabilis; Urochloa ruziziensis; Fixação biológica de nitrogênio; Adubação nitrogenada; Phaseolus vulgaris; Inoculação de bactérias; Bactérias promotoras de crescimento; Biological nitrogen fixation; Nitrogen fertilization; Phaseolus vulgaris; Inoculation of bacteria; Growth-promoting bacteria